PENERAPAN MODEL GROUP INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR PADA MATERI MOMENTUM DAN IMPULS - Natalia, Devi Clarisa; Maria, Haratua Tiur; Hamdani, Hamdani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe aim of this research is to improve students’ learning outcomes through Group Investigation model on momentum and impulse content The design of this study is in the form of a non-equivalent control group which involve 66 students of SMA Kemala Bhayangkari that taken from X Mia 1 and X Mia 2. Data collection includes students’ achievement test in the form of pretest and posstest which consist of 5 multiple choice questions and 2 Essay questions, questions are made in parallel. Subject of the research is students of SMA Kemala Bhayangkari 1 Pontianak with 66 students that taken from X MIA 1 class and X MIA 2 class. The data is obtained by using pretest and posttest. In doing Pretest on experimental class, the average of the pretest is 34,18 and posttest 75.15, in control class, the average of pretest is 38,71 and posttest is 71.13. The result of the research shows that there is a different improvement between experimental class and control class with 10% of increasing and 35% for the effectiveness of model in moderate category. Hence, Applying Group Investigation model can improve students’ learning outcomes in learning momentum and impulse. Keywords: Learning Outcomes, Group Investigation, Momentum and Impulse